Prevalence of taurodontism: meta-analysis in recent humans and evolutionary perspectives - Pierre-Hadrien Decaup; Christine Couture; Mathieu Colin; Elsa Garot (Homo)
Taurodontism is a continuous anatomical variation of permanent and primary posterior teeth represented by an enlargement of the pulp cavity. A high prevalence of the trait is reported in Homo neanderthalensis remains. Exploring and refining epidemiology of taurodontism in actual populations could strengthen the hypothesis of a selective advantage for a high attrition diet (as heavy tooth wear in Homo sapiens evolution changed little until recently) or favour pleiotropic or genetic drift effects to explain the high frequency of the trait in Neandertal remains. Prevalence ranges between 0.1% and 48% in the literature. The aim of the present study is to assess the prevalence of taurodontism in recent populations by means of meta-analysis, that is, is the prevalence of taurodontism lower or higher in modern human living populations, where the selective advantages of high attrition diet are still expected? From 90 potentially eligible studies, 15 were included in the meta-analysis. Only cross-sectional studies were reported, and 14,771 participants were included. The meta-analyses were performed with a random model, calculating a weighted-mean prevalence of 11.8%. Gender was found to be unrelated to the prevalence of taurodontism (OR = 0.84 (95% CI 0.67–1.05), p > 0.05). Taurodontism occurs in approximately 11.8% of the living population. This result questions the status of taurodontism as a “typical trait” in Homo neanderthalensis and allows a possible common evolutionary mechanism in Homo sapiens and Homo neanderthalensis for the trait. Further studies should include more accurate and standardized methods to assess the condition.